Sloan Great Wall as a complex of superclusters with collapsing cores - Einasto M; Lietzen H; Gramann M; Tempel E; Saar E; Liivamagi LJ; Heinamaki P; Nurmi P; Einasto J (EDP SCIENCES S A, 2025)
Context. The formation and evolution of the cosmic web is governed by the gravitational attraction of dark matter and antigravity of dark energy (cosmological constant). In the cosmic web, galaxy superclusters or their high-density cores are the largest objects that may collapse at present or during the future evolution.Aims. We study the dynamical state and possible future evolution of galaxy superclusters from the Sloan Great Wall (SGW), the richest galaxy system in the nearby Universe.Methods. We calculated supercluster masses using dynamical masses of galaxy groups and stellar masses of galaxies. We employed normal mixture modelling to study the structure of rich SGW superclusters and search for components (cores) in superclusters. We analysed the radial mass distribution in the high-density cores of superclusters centred approximately at rich clusters and used the spherical collapse model to study their dynamical state.Results. The lower limit of the total mass of the SGW is approximately M = 2.5 x 10(16) h(-1) M-circle dot. Different mass estimators of superclusters agree well, the main uncertainties in masses of superclusters come from missing groups and clusters. We detected three high-density cores in the richest SGW supercluster (SCl 027) and two in the second richest supercluster (SCl 019). They have masses of 1.2-5.9 x 10(15) h(-1) M-circle dot and sizes of up to approximate to 60 h(-1) Mpc. The high-density cores of superclusters are very elongated, flattened perpendicularly to the line of sight. The comparison of the radial mass distribution in the high-density cores with the predictions of spherical collapse model suggests that their central regions with radii smaller than 8 h(-1) Mpc and masses of up to M = 2 x 10(15) h(-1) M-circle dot may be collapsing.Conclusions. The rich SGW superclusters with their high-density cores represent dynamically evolving environments for studies of the properties of galaxies and galaxy systems.